Investigating self-assembled protein nanotubes using atomic force microscopy - Niu, Lijiang (2009)
Self-assembled protein nanotubular materials are attractive as putative building blocks for a variety of applications. Knowledge of the three-dimensional structures and the physical properties of these protein nanotubes then becomes a prerequisite for their use in rational materials design. The main purpose of the work presented in this thesis is to investigate both the structural and mechanical properties of protein nanotubes utilizing atomic force microscopy (AFM). Several different protein nanotubes will be used as exemplars to develop AFM methods. AFM is capable of both visualizing and monitoring dynamic processes. Within this thesis, not only could the change in morphology of protein nanotubes be visualized by AFM, but also changes in their mechanical properties were monitored as dynamic processes. For example, changes in the morphology (in chapter 3) and flexibility (in chapter 4) of lysozyme fibrils during fibrillization were investigated. Chapters 4 to 6 describe a range of different methods to obtain the mechanical properties of protein nanotubes: the persistence length method (chapter 4), the adhesive interaction method (chapter 5) and the bending beam method (chapter 6). All of these had their own advantages. However, each method was found only to be suitable for protein nanotubes with elasticities within a defined range. The protein nanotubes investigated by AFM in the thesis included Salmonella flagellar filaments, lysozyme fibrils and diphenylalanine (FF) nanotubes. All of the investigated protein nanotube structures had Young’s moduli lying between that of gelatin and bone. This highlights their potential, in terms of mechanical properties, for a range of applications in drug-delivery systems and tissue-engineering scaffolds. In future, if a database of mechanical properties of protein nanotubes could be built up using the AFM methods developed and utilized within this thesis, the development of the applications of protein nanotubes will be accelerated, as the right protein nanotubes will be selected for appropriate applications.